2021
DOI: 10.1088/1755-1315/765/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified palm kernel shell biochar for the removal of heavy metals from aqueous solution

Abstract: Heavy metals eradication from water is a complicated subject, therefore a viable, resilient, and green technology is imperative. Heavy metal removal can be accomplished through easy access, economical, and efficient sorbents derived from agricultural waste. In the current study, palm kernel shell (PKS) waste was converted into biochar (PKSC) via pyrolysis. Chemical modification was performed on PKSC via acid-base treatment to refine its adsorption properties. Batch experiments were conducted to study the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Imran-Shaukat et al [122] reported the post-treatment of palm shell-derived biochar with 20% NaOH followed by acid treatment (HCl) to remove heavy metals from an aqueous solution. Samsuri et al [123] reported the application of Fe (III)-coated biochar for the removal of As (III) and As (V) from the aqueous solution, which was developed by impregnation of biochar particles with Fe ions in a solution containing FeCl 3 salt for 24 h. Lyu et al [124] reported the post-treatment of biochar with 0.063 moles of FeSO 4 aqueous solution to produce FeS-coated biochar particles to remove hexavalent chromium from the aqueous solution.…”
Section: (B) Post-treatment Methodsmentioning
confidence: 99%
“…Imran-Shaukat et al [122] reported the post-treatment of palm shell-derived biochar with 20% NaOH followed by acid treatment (HCl) to remove heavy metals from an aqueous solution. Samsuri et al [123] reported the application of Fe (III)-coated biochar for the removal of As (III) and As (V) from the aqueous solution, which was developed by impregnation of biochar particles with Fe ions in a solution containing FeCl 3 salt for 24 h. Lyu et al [124] reported the post-treatment of biochar with 0.063 moles of FeSO 4 aqueous solution to produce FeS-coated biochar particles to remove hexavalent chromium from the aqueous solution.…”
Section: (B) Post-treatment Methodsmentioning
confidence: 99%
“…Studies conducted on various adsorbents treated with NaOH have indicated that the Langmuir, Freundlich, and Sips models offer better descriptions of the Ni(II) equilibrium adsorption process. In these studies, the adsorption capacities for Ni(II) were found to be 0.2, 0.123, and 41.75 mg/g using pineapple shell [64], peanut shell [44], and palm biochar [40], respectively. It was determined that the Langmuir model best fits the experimental data for the adsorption capacity of WL treated with HCl [32], methanol and acetonitrile [54], and citric acid [48].…”
Section: Ni(ii) and Cu(ii) Adsorption Isotherms Using Wlw And Wlnmentioning
confidence: 97%
“…In the case of WLN, the percentage of removal decreased from 58% to 37% for Ni and from 37% to 30% for Cu. This was due to the effect that occurred when the concentration of sites for the adsorption of metal ions remained constant, resulting in greater ease of disposition at these sites at low metal concentrations but preventing further metals from being removed from solution when the available sites became saturated [39][40][41][42][43][44][45].…”
Section: Effect Of the Initial Concentration Of Metals On Adsorption ...mentioning
confidence: 99%
See 2 more Smart Citations